Evaluación de los factores de riesgos psicosociales y elaboración de un plan de mitigación para el personal de salud de servicio de emergencia del hospital Luis. G. Dávila de la ciudad de Tulcán. - Lima Montalvo, Andrés Ramiro (2017)
This research project details an analysis of the factors related to the psychosocial risk factors and their impact on the work performance of the health professionals of the emergency service of the “Luis G. Dávila” Hospital in the Tulcán city. A subject of great importance within the institutions, since it seeks to have a climate suitable for the work in which the workers perform their functions, with a single purpose, levels of quality and warmth reflected in a high work performance and patient satisfaction . The main objective of the study was to evaluate psychosocial risk factors and to develop a mitigation plan to improve the work performance of the emergency personal service. The investigation was carried out in the 31 health professionals of the emergency service. The information obtained was collected through the Navarro Questionnaire to assess the psychosocial risk factors and the evaluation of the work performance was done through SENRES - EVAL-01 of the Ministry of Labor. The results were tabulated and interpreted to define the relationship between these two variables. Through the investigation it was possible to verify the risk factors that influence the workers' labor performance: participation in the work, labor responsibility, technical training, clarity in the information, channels of communication and time management. These factors must be worked through a mitigation plan that minimizes the incidence of these factors on the worker and their work performance.